2002
DOI: 10.1099/00207713-52-2-437
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter nemestrinae ATCC 49396T is a strain of Helicobacter pylori (Marshall et al. 1985) Goodwin et al. 1989, and Helicobacter nemestrinae Bronsdon et al. 1991 is therefore a junior heterotypic synonym of Helicobacter pylori.

Abstract: NOTE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…As the G+C content was markedly lower than all other known Helicobacter species (24 mol%) a re-appraisal was undertaken. Sequence analysis of seven housekeeping genes and two flagellin genes from the single strain of H. nemestrinae (ATCC 49396 T ) showed that all sequences clustered with those from multiple isolates of H. pylori (Suerbaum et al 2002). Repeat sequence analysis of the 16S rRNA gene of H. nemestrinae showed that it differed by 38 bp from that previously reported and was less than 1 % different from multiple H. pylori strains.…”
Section: Helicobacter Nemestrinaementioning
confidence: 82%
See 1 more Smart Citation
“…As the G+C content was markedly lower than all other known Helicobacter species (24 mol%) a re-appraisal was undertaken. Sequence analysis of seven housekeeping genes and two flagellin genes from the single strain of H. nemestrinae (ATCC 49396 T ) showed that all sequences clustered with those from multiple isolates of H. pylori (Suerbaum et al 2002). Repeat sequence analysis of the 16S rRNA gene of H. nemestrinae showed that it differed by 38 bp from that previously reported and was less than 1 % different from multiple H. pylori strains.…”
Section: Helicobacter Nemestrinaementioning
confidence: 82%
“…However, 16S rDNA analysis may not differentiate closely related strains or species within the Helicobacter genus due to their high sequence similarity. Moreover, analysis based on the 16S rRNA gene does not necessarily correspond to the results of polyphasic taxonomy Vandamme et al 2000;Suerbaum et al 2002;O'Rourke et al 2004). Indeed, gene analysis of the 60 kDa heat-shock protein (HSP60) has been demonstrated to have a higher resolution than the conventional 16S rRNA gene for species identification of gastric and enterohepatic Helicobacter species (Mikkonen et al 2004).…”
Section: Molecular Analyses Phylogenymentioning
confidence: 95%
“…Basic nucleotide BLAST alignment (Blastn) of this sequence demonstrated complete homology with 74 H. pylori strains, two H. nemestrinae and four Helicobacter sp. “liver” (that were subsequently found to be indistinguishable from H. pylori [26], [27]), and 17 uncultured Helicobacter species. Sequences of these uncultured Helicobacter species had been determined from biopsies from human esophageal carcinoma or inflamed colon [28], from the stomach of cheetahs [a carnivore that is frequently colonized by the closest H. pylori relative, H. acinonychis [29]], or from the stomach of thoroughbred horses [30].…”
Section: Resultsmentioning
confidence: 99%
“…On occasion, descriptions have been controversial [6][7][8][9], and on several occasions the ICSP Subcommittee on the Taxonomy of Campylobacter and Related Bacteria have remarked on the sometimes questionable quality of particular species descriptions that were observed [10][11][12]. Furthermore, taxonomic methods have undergone a 'sea change' with whole-…”
Section: Introductionmentioning
confidence: 99%